Venereal Diseases Treatment for Merauke’s Marind (Marind-Anim) Tribe in the Dutch Colonial Period - Rosmaida Sinaga; Hafnita Sari Dewi Lubis; Yushar Tanjung; Lister Eva Simangunsong (IHiS (Indonesian Historical Studies), 2022)
This article provides some proofs that influenced the increasing number ofMarind-Anim people who suffering from venereal diseases. It also providesfactual efforts that had been done by the colonial government as well as Catholicmissionaries in Merauke to overcome this problem. This study applies historicalmethods with four stages: heuristics, verification (internal and external criticism),interpretation/explanation and historiography. Primary sources obtained fromNational Archives of the Republic of Indonesia i.e., Memorie van Overgave van hetBestuur over de Afdeeling Zuid Nieuw Guinea; letter of the Minister of Colonies to theGovernor General of the Dutch East Indies; Report of Assistant Resident ZuidAfdeeling Nieuw Guinea to the Director of Government; and official printed sources,e.g., Volkstelling 1930. Michel Foucault's power relations theory is used to analyzethe causes of venereal disease in the Marind Tribe. The results shows that the causeof the increasing number patients who had venereal disease in the Marind tribe,Merauke, was related to their traditional understanding which legalized free sexand deviant sexual activities in the Marind tribe. The imbalanced power relationsbetween men and their wives and between men and adolescence men causingvenereal diseases and sexual perversions in the Marind Tribe. The strategyimplemented by the colonial government was to involve Catholic missionarieswho were trusted to overcome the disease by building a housing model that canonly be occupied by nuclear families who are not infected with venereal diseases.The colonial government demolished men’s houses because there werepossibilities of homosexual intercourses which become one of the causes ofvenereal disease among the Marind Tribe. In addition, the government requiredthe cenderawasih bird hunterers to have their genital health checked as a huntingpermit. The government built hospitals and clinics and invented doctors whospecialize in venereal disease to treat the patients. These strategies has succeededin treating and eradicating venereal diseases among the Marind Tribe.